Young Avengers. [3] Mic-drop at the edge of time and space - Gillen, Kieron; Wilson, Matthew 1981-.; Mckelvie, Jamie (New York Marvel, 2014)
They say you can never go home. For the Young Avengers, that's not true. They can go home--it's just that if they do, the universe may end. Better not go home then, eh? (Wait, what are you doing, Young Avengers? You've decided to go home?!?) The team takes on the gig to save reality, but is Kate Bishop an enemy in waiting? Is this the last we see of the loveable/ strangle-able Kid Loki?--p. [4] of cover.
"Contains material originally published in magazine form as Young Avengers #11-15."
UCWS-2014-G-2024 donated by Dr. Aries Arugay
Keywords: Young adult fiction; Science fiction comic books, strips, etc; Heroes -- Comic books, strips, etc; Loki (Norse deity) -- Comic books, strips, etc; America, Captain (Fictitious character) -- Comic books, strips, etc; Avengers (Fictitious characters) -- Comic books, strips, etc; Graphic novels